2020
DOI: 10.1094/pdis-10-19-2077-re
|View full text |Cite
|
Sign up to set email alerts
|

Eight Colletotrichum Species, Including a Novel Species, Are Associated With Areca Palm Anthracnose in Hainan, China

Abstract: Genus Colletotrichum is one of the most important genera of plant-pathogenic fungi affecting numerous species, particularly tropical and subtropical crops and fruit trees. In this study, 43 Colletotrichum strains were isolated from areca palm leaves with anthracnose symptoms in 11 areca palm plantations in eight counties of Hainan, China. Based on the morphology, phylogenetic analysis of six loci (internal transcribed spacer, actin, chitin synthase 1, glyceraldehyde-3-phosphate dehydrogenase, β-tubulin, and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 43 publications
3
14
0
Order By: Relevance
“…Plant‐pathogenic Colletotrichum species are often described as causing typical symptoms of anthracnose disease, including spots and sunken necrotic lesions on leaves, stems, flowers, and fruits, but they can cause other symptoms such as red rot on sugar cane, crown rot on strawberry and banana, and brown blotch on cowpea (Cannon et al, 2012). Anthracnose is an important disease of rubber tree, coffee, and areca palm in Hainan, resulting in significant yield losses (Cao et al, 2019a, 2019b, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Plant‐pathogenic Colletotrichum species are often described as causing typical symptoms of anthracnose disease, including spots and sunken necrotic lesions on leaves, stems, flowers, and fruits, but they can cause other symptoms such as red rot on sugar cane, crown rot on strawberry and banana, and brown blotch on cowpea (Cannon et al, 2012). Anthracnose is an important disease of rubber tree, coffee, and areca palm in Hainan, resulting in significant yield losses (Cao et al, 2019a, 2019b, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It has been confirmed that C . siamense is the dominant species that causes anthracnose on these three crops in Hainan (Cao et al, 2019a, 2019b, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…( 2017 ) Areca catechu Arecaceae Areca palm, betel palm Cao et al. ( 2020 ) Artocarpus heterophyllus Moraceae Jackfruit CDFA ( 2016 ) Aucuba japonica Garryaceae Aucuba Li et al. ( 2016a , b ) Camellia oleifera Theaceae Tea oil camellia Li et al.…”
Section: Appendix a – Colletotrichum Fructicola Host Plantsmentioning
confidence: 99%
“…Recent research and animal studies demonstrate that Areca palm possesses a variety of therapeutic properties, including antibacterial [ 13 , 14 ], antifungal [ 14 , 15 ], antiparasitic [ 14 , 15 ], antioxidant [ 15 , 16 ], anti-inflammatory [ 15 ], analgesic [ 15 ], hepatoprotective [ 17 ], hypoglycemic [ 18 ], antiulcerogenic [ 19 ], wound healing [ 16 ], antidepressant [ 20 ], antifertility [ 21 ], abortifacient, and anti-implantation [ 22 ] effects.…”
Section: Introductionmentioning
confidence: 99%